Investigation and optimization of the piezoelectric nanocomposite ZnO/PVVH/P(VDF-TrFE) for energy harvesting applications - A. Sarhan; A. Hassan; M. I. Abdelhamid; T. Fahmy; A. Habib (Scientific Reports)
Abstract 30/70 wt.% poly (vinyl chloride-co-vinyl acetate-co-2-hydroxypropyl acrylate) (PVVH) / poly (vinylidene fluoride-co-trifluoroethylene) P(VDF-TrFE) polymer blend (PB) are prepared and doped with various content of Zinc oxide nanoparticle (ZnO NPs) using casting technique. X-ray diffraction (XRD), Fourier transform infrared (FT-IR), Transmission electron microscopy (TEM), UV–Vis and Thermogravimetric analysis (TGA) are used for structural, optical and thermal properties investigation. XRD results revealed that the crystallinity degree of PB is enhanced from 83.8 to 92.3% upon increasing the ZnO NPs. FTIR analysis showed a shift in position of some characteristic bands, confirming the complexation between ZnO NPs and functional groups of PB. UV–Vis analysis showed that both direct and indirect energy gaps (E dg /E ig ) are reduced from (4.08/2.34) for PB to (3.65/1.99) eV for 1.25 wt% ZnO/PB nanocomposite. Thermally stimulated depolarization current (TSDC) measurements demonstrated that the phase transition from ferroelectric to paraelectric phase occurred at 343 K for PB and increased to 350 K after embedding ZnO NPs. Thermal sampling (TS) technique is applied and thermodynamic parameters are estimated. Piezoelectric coefficient (d33) is optimized from 12.8 pC/N for PB sample to 23.7 pC/N for 1wt.% ZnO/PB nanocomposite at 6.24 × 105 Pa. Our results give a prediction for new piezoelectric material design capable for various energy harvesting applications.